Артефакти попередніх епох як об’єкти шанування давнім населенням (за матеріалами археологічних пам’яток Буковини) - Калініченко, Віталій; Пивоваров, Сергій (Чернівці, Чернівецький національний університет імені Юрія Федьковича, 2024)
Стаття присвячена аналізу матеріалів, виявлених під час дослідження археологічних пам’яток Буковини, які не вписуються в їхній історичний та хронологічний контекст. Мова йде про знаряддя праці, озброєння, прикраси, предмети побуту попередніх епох: від доби палеоліту до ранньозалізного часу. Такі знахідки тривалий час не знаходили задовільних пояснень в історіографії. Артефакти попередніх епох отримали в науковій літературі назву «громові стріли». Для їх позначення в роботах використовується позначення «антикварний» виріб чи «антикваріат». В історіографії «громові стріли вважали наслідком зміщення культурних пластів на багатошарових пам’ятках, пізніми перекопами, або взагалі замовчували, так як, вони не знаходили пояснень. Значну допомогу у вирішенні цієї проблеми надали етнографічні дослідження. У європейського населення «громові стріли» асоціювалися із різноманітними кам’яними, рідше металевими, виробами, а саме—просвердленими неолітичними та енеолітичними кам’яними сокирами, палеолітичними наконечниками списів, гостроконечниками, крем’яними ножами, бронзовими наконечниками стріл. До їх числа також відносять фульгуріти (пісок, який сплавився від удару блискавки) та белемніти (скам’янілі молюски) тощо. Можемо говорити, що кам’яні та металеві сокиривиконували функцію оберегів, очевидно, для вищих прошарків тогочасного суспільства та були «лікувальними» засобами, які освячувалися церквою та використовувалися населенням. The article is devoted to the analysis of archaeological materials discovered during the study of archaeological places of Bukovyna, which do not fit into their historical and chronological context. We are talking about objects, the use of which is clearlyanachronistic. These are tools, weapons, decorations, household items of previous eras: from the Paleolithic to the Early Iron Age. Discovered at the places of the ancient and medieval periods, such finds did not find satisfactory explanations in historiography for a long time. Artifacts of previous eras received the general name «arrows of thunder» in the scientific literature. At the same time, in a number of works, mainly archaeological, the designation «antique» product or«antique» is used to designate them. «Arrows of thunder» discovered at the places of the ancient and medieval periods did not find satisfactory explanations in historiography. For the most part, they were considered to be the result of the displacement of cultural layers at multi–layered monuments, late excavations, or they were generally silenced, since they did not find satisfactory explanations. However, when such objects were discovered in closed archaeological complexes and the chance of their getting there was ruled out, there were attempts to explain this phenomenon.Ethnographic studies and folklore materials provided significant help in solving this problem. Among the European population, «arrows of thunder» were associated with various stone, less often metal, products, namely, drilled Neolithic and Eneolithic stone axes, Paleolithic spearheads, sharp points, flint knives, bronze arrowheads, etc. They also include fulgurites (sand that melted from a lightning strike) and belemnites (fossilized molluscs), etc. We can say that stone and metal axes performed the function of amulets, obviously, for the higher strata of society at that time and were «healing» means that were consecrated by the church and used by the population. It should be mentioned that «heavenly axes in a golden frame» are known in Byzantium, and the fact of the consecration of an ax by a bishop from Scandinavian warriors is recorded in written sources.It is much more difficult to explain the presence of metal ornaments (fibulas) of previous eras in the Chorniv settlement and their content. We believe that these were relics somehow connected with the church and its saints. In Christian iconography, sinceByzantine times, one of the elements of clothing in which Jesus Christ, the Mother of God, Saints and Great Martyrs were depicted was a clasp or fibula. It was used to fasten the edges of the hymantia, chlamydia, lazerna, that is, the upper parts of the clothes (cloaks) that covered the figures of the righteous Christians. Fibulas (they are also called zapons or agraphs) are especially often found on icons with images of holy martyrs and pious princes. Later, the image of fibulas on the cloaks of soldiers became a symbol of serving the Heavenly King—the Lord Jesus Christ and joining his Holy Army. So, we can assume that the fibula in the iconography symbolized belonging to the army that protected the Christian religion. It is not excluded that not only fibulas-fasteners were symbols of warriors-defenders, but also real metal fibulas found under different circumstances or brought from places connected with the lives and exploits of the saints-great-martyrs could serve as Christian amulets for ancient Ukrainian warriors and be objects of veneration and adoration.
Artifacts of previous eras, as objects ofreverence by ancient populations (based on the materials of the archaeological places of Bukovyna)
Keywords: Буковина; археологічні дослідження; Чорнівське городище; Рідківецький археологічний комплекс; матеріальна культура; артефакти; "громові стріли"